Efeito das dietas restritivas em pacientes com obesidade: uma revisão sistemática - Gobatto, Filipe Euclides (2023)
Introduction: The prevalence of obesity, a chronic and multifactorial disease, has been exponentially increasing worldwide over the years, including in Brazil. In an attempt to reduce or control their own weight, people generally tend to seek restrictive diets to achieve this goal, something that causes endocrine and metabolic changes in their bodies. Objective: To determine the effects of restrictive diets on obese patients. Methods: A systematic literature review was conducted using the PICO strategy and the PRISMA protocol recommendations. The databases used for article collection were Scielo, PubMed, LILACS, EMBASE, Cochrane, and Rendalyc. Randomized articles published between 2013 and 2022 were included, published in English, Portuguese, and Spanish. The selected articles were grouped in the Ryylan platform. The quality assessment of evidence was done using the RoB 2.0 tool. Results: This systematic review included 13 articles. The intervention period varied greatly among the articles. Only 2 articles did not provide information regarding weight loss during the implementation of restrictive diets. According to the articles that presented data on weight loss, restrictive diets are useful in achieving this goal. However, according to 6 articles that evaluated weight maintenance after the use of this strategy, it became evident that there is, to some extent, weight regain. Another important finding is that restrictive diets cause endocrine and metabolic changes in individuals who practice them. Finally, the samples used in the studies had little ethnic diversity, which may lead to divergent results in future studies. Conclusion: Restrictive diets cause physiological changes in obese patients, but further studies with more ethnically diverse samples are still needed to determine if these results are valid for the entire population